Economic implications of a fungus, Cordyceps sinensis on scheduled tribes of high altitudes of Pithoragarh, Uttrakhand, India - Bhatt, Nirmala (Mushroom Research, 2012)
Uttrakhand a hill state of India is gifted with a rich mushroom flora that includes one of the most valuable medicinal mushrooms Cordyceps sinensis, which parasitizes the larvae of a moth of the genus Hepialus and survives in alpines grasslands of the high altitudes of Himalayas ranging from 3000m-5000m. Tibetans know this fungus as Yartsa Gumbu, (summer grass –winter worm), and locally in Pithoragarh as ‘Keera Ghas’ (insect herb). Collection and trade of this caterpillar fungus is one of the most important sources of income for scheduled tribes of district Pithoragarh, Uttrakhand. It has tremendous impact on the economy of scheduled tribes and often derives over 70% of their annual cash income from its collection. A family of four to five collects about half to one kilogram C. sinensis and in two to three months period they earn over 1.0-2.0 lakhs or more which is enough to sustain them for rest of the year. Since last few years Cordyceps has been traded very extensively in Dharchula and Munsyari blocks of Pithoragarh, Uttrakhand. The estimated volume of trade in Uttrakhand was 1250-1800 kg/year during last five years from 2004 to 2008. The fungus brought to the market by local gatherers particularly scheduled tribes of high altitudes and sold to agents or brokers in Munsyari and Dharchula which was further forwarded by them to traders comes from Delhi, Nepal, Bhutan and Tibet. Some brokers or traders buy the Cordyceps directly from the gatherers in the villages Chipla, Ralam, Laspa, Burfa, Karschila, Budhi Galja, Chalm, Boin, Bon, Dugtu, Panchachuli, Nampa and Api of high altitudes in Pithoragarh. In fact, there is no organized trade for the product so far. Therefore, price varied at the level of gatherers and brokers in different years from Rs. 0.6 to Rs. 3.50 lakh and Rs. 0.9 to Rs. 5.00 lakh, respectively during the year 2004 to 2008.